(untitled) (Balneo and PRM Research Journal, 2021)
Introduction. Burning mouth syndrome (BMS) is a clinical condition characterized by the presence of chronic pain in absence of clinically visible lesions of the oral mucosa. The etiology is uncertain and the therapeutic strategies still controversial. The objective of this prospective study is to analyze the efficacy of essential oils-based mouthwashes in the therapy of BMS. Material and method. This study included 16 patients affected by BMS who were treated with essential oils-based mouthwashes and glucose solution on alternated days for 30 days. Symptomatology was evaluated after 15, 30 and 90 days. Results and discussions. A the end of the treatment, most of the patients (67%) referred an improvement of symptoms up to complete remission in 90 days. Conclusions. Based on this study, essential oils-based mouthwashes could represent a valid aid in the treatment of BMS. Further studies are necessary in order to identify effective and standardized therapeutic protocols.